1998
DOI: 10.1021/bi9724671
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Distribution of α-Helices in the Colicin B and E1 Channel Domains:  A One and Two Dimensional 15N Solid-State NMR Investigation in Uniaxially Aligned Phospholipid Bilayers

Abstract: Thermolytic fragments of the channel-forming bacterial toxins colicin B and colicin E1 were uniformly labeled with the 15N isotope and reconstituted into uniaxially oriented membranes. These well-aligned samples were investigated by proton-decoupled 15N solid-state NMR spectroscopy at 40.5 and 71.0 MHz. The one dimensional spectra indicate a predominant orientation of the colicin alpha-helices parallel to the bilayer surface but also the presence of a considerable proportion of peptide bonds that align in a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…7 and 8). This is in excellent agreement with previous structural findings for the colicin A pore-forming domain (19,25) as well as the high degree of primary sequence homology between the pore-forming fragments of ColA and ColB (16). The calorimetric, fluorescence, and circular dichroism studies presented in this paper demonstrate that the two reported transitions of ColB are due to denaturation of two discrete domains of the protein.…”
Section: Structural and Functional Characteristics Of Colicin B Andsupporting
confidence: 92%
See 3 more Smart Citations
“…7 and 8). This is in excellent agreement with previous structural findings for the colicin A pore-forming domain (19,25) as well as the high degree of primary sequence homology between the pore-forming fragments of ColA and ColB (16). The calorimetric, fluorescence, and circular dichroism studies presented in this paper demonstrate that the two reported transitions of ColB are due to denaturation of two discrete domains of the protein.…”
Section: Structural and Functional Characteristics Of Colicin B Andsupporting
confidence: 92%
“…The full-length protein as well as its thermolytic fragment were purified following procedures described elsewhere (15,16). This latter domain of the homologous colicin A protein has been shown to exhibit pore-forming activities (e.g.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structurally, Bcl-x L ΔTM is most similar to the translocation domain of diphtheria toxin (23). For this toxin, as well as others, membrane association is mediated in part by the so-called hydrophobic, helical hairpin, which corresponds to α-helices 5 and 6 in Bcl-x L ΔTM (Figure 5a) (38)(39)(40)(41)(42)(43)(44)(45)(46). Despite the structural similarity, the sequences of these proteins are less than 19% identical, and they possibly are an example of convergent evolution toward a versatile protein fold.…”
Section: Two Acidic Residues In the Conserved Hairpin And The Conformmentioning
confidence: 99%